2007
DOI: 10.1016/j.ypmed.2007.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Concordance of population-based estimates of mammography screening

Abstract: Objective-Estimates of adherence to mammography screening guidelines vary, in part, due to lack of consensus on defining adherence. This study estimated adherence to repeat (two successive on-time screenings) and regular screening (three or more successive screenings) and evaluated the impact of varying operational definitions and evaluation periods.Methods-The study included women aged 50-80 without a history of breast cancer who: were on a biennial screening cycle and due for a screening mammogram between 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 40 publications
3
12
0
1
Order By: Relevance
“…The rate of mammography maintenance we report here is similar to rates reported in two previous studies of mammography adherence that examined screening behavior across three or more screening cycles (range: 42 – 56%) (20, 30). However, we expected more women to maintain mammography screening, due to unique characteristics of this sample.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The rate of mammography maintenance we report here is similar to rates reported in two previous studies of mammography adherence that examined screening behavior across three or more screening cycles (range: 42 – 56%) (20, 30). However, we expected more women to maintain mammography screening, due to unique characteristics of this sample.…”
Section: Discussionsupporting
confidence: 85%
“…Overall, it was a group that should have been especially likely to receive continued mammograms. The modest maintenance rate may reflect, in part, our analyses that used an approximately annual screening interval (although with a 14-month window), a criterion that yields fewer adherent women than does the use of longer intervals (30, 45). Yet, the odds of not getting screening mammograms decreased over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first asked, “On a scale from 0 to 100%, where 0 = certain not to happen and 100 = certain to happen, how likely are you to get breast cancer in your lifetime?” The second asked, “Compared with other women your age, how likely are you to get breast cancer in your lifetime?” Responses ranged from “much below average” to “much above average.” The outcomes of interest were use of screening mammography and CBE within 15 months, as well as genetic testing. Extending the screening interval for mammography and CBE beyond the standard 12 months allows flexibility for factors such as wait-times at imaging facilities [39,40]. Self-reported dates and reasons for screening examinations were obtained from the year 1 PHSQ .…”
Section: Methodsmentioning
confidence: 99%
“…Timeframe notwithstanding, rates of repeat mammography are low. Less than 50% of women obtain two consecutive mammograms on schedule [6,7] with estimates ranging between 20 and 92% [7][8][9]. Another study [8] found that only 42% of women reported 3?…”
Section: Introductionmentioning
confidence: 99%